The Prevalence of Children's Postural Abnormalities and Its Association with Sport Activity - Razieh Karimian; Maryam Karimian; Mojtaba Hadipour; Fatemeh Heyat; Azam Janbozorgi (Fasa University of Medical Sciences, 2016)
Background & Objective: The future of each society is based on its youth. In addition, the physical-mental health as well as the presence of healthy and capable people is a considerable requirement for all the societies. Thus, the aim of this research was to study the prevalence rate of children's postural abnormalities and its relationship with sport activity. Materials & Method: 148 children (74 boys and 74 girls) were randomly selected. The research tools were plummet (guideline), matrix sheet, mirror box and the personal characteristics questionnaire. All the results were analyzed by using chi-square, freedman statistical method and the spearman correlation coefficient. Result: The results indicated that there is a significant difference between the two normal and abnormal height structure states (p≤0.01). Similarly, there was a significant negative difference between the number of skeletal abnormalities and the exercise activities in girls (r= 0.355) and boys (r= 0.369). In the case of abnormalities comparison between the sexes, the freedman test results indicated that there is a significant difference between the ranking of the boys' skeletal abnormalities as compared to the girls, in a way that the dorsal lord sis and flat back were the highest and the lowest in the girls, respectively. Moreover, the results of the person correlation coefficient test indicated that there is only a positive significant relationship between the age of the girls and the number of skeletal abnormalities (p≤0.01, r=0.586). Conclusions: According to the results of this research, it can be stated that majority of the children at least have single skeletal abnormality, resulted from some factors such as heredity, daily wrong habits, and non standard equipments and facilities. In addition, not attending the related sports activities may increase the chance of these skeletal abnormalities.